Konya : the land of peace and love - Birekul, Mehmet (Kültür A.Ş, 2007)
This guide book will take the visitors to the capital city of the Selçuk Empire where is the centre of the night of colour of turquoise with its modern buildings, Konya is an Anatolian city, which whispers peace and calm to the ear of people. A modern and a young viewpoint of the city stands like a promenade areas in the middle of the city. It is possible to meet associations that serve in the historical places on the streets. A bunch where is from beautiful place that surrounds you with its history and nostalgia traces that you are able to fell always in every street.